Credit and the natural rate of interest. - Fiorella De Fiore; Oreste Tristani (European Central Bank (ECB), 2008)
We analyze the properties of the natural rate of interest in an economy where nominal debt contracts generate a spread between loan rates and the policy interest rate. In our model, monetary policy has real effects in the flexible-price equilibrium, because it affects the credit spread. Relying on a definition suitable for this environment, we demonstrate that: (i) the natural rate is independent of monetary policy and (ii) it delivers price stability, if used as the intercept of a monetary policy rule. The second result holds exactly if real balances are remunerated at a constant spread below policy interest rates, approximately otherwise. We also highlight, however, that the natural rate is not robust to model un-certainty. The natural rate reacts differently to aggregate shocks - not only quantitatively but also qualitatively - depending on the underlying model assumptions (e.g. whether or not financial markets are frictionless).
Keywords: E40; E50; G10; 330; credit frictions; monetary policy; Natural rate of interest; Geldpolitik; Zins; Kreditmarkt; Theorie